2005
DOI: 10.1111/j.1600-0404.2005.00488.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between microtubule-binding repeats and morphology of neurofibrillary tangle in Alzheimer's disease

Abstract: Objective –  The present study was performed to compare the distributions of three‐repeat (3R) and four‐repeat (4R) neurofibrillary tangles (NFT) with those of pretangles (p‐NFT), intracellular NFT (i‐NFT), and extracellular NFT (e‐NFT) in the hippocampus of Alzheimer's disease brains. Methods –  NFT labeling was performed using anti‐tau antibodies: pSer262 for p‐NFT, pSer422 for i‐NFT, AT8 for e‐NFT, RD3 for 3R, and RD4 for 4R tau, and Gallyas impregnation for the NFT population. RD4‐ and pSer422‐positive NFT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(36 citation statements)
references
References 32 publications
3
33
0
Order By: Relevance
“…These findings are compatible with previous observations that pretangle neurons are positive for 4R tau and ghost tangles are positive for 3R tau (Espinoza et al 2008;Iseki et al 2006;Jellinger and Attems 2007;Kitamura et al 2005;Lace et al 2009). However, this correlation may be debatable if the diffuse cytoplasmic staining of RD3 noted previously (de Silva et al 2003) actually represents the non-fibrillary tau deposits found in pretangles.…”
Section: Discussionsupporting
confidence: 94%
“…These findings are compatible with previous observations that pretangle neurons are positive for 4R tau and ghost tangles are positive for 3R tau (Espinoza et al 2008;Iseki et al 2006;Jellinger and Attems 2007;Kitamura et al 2005;Lace et al 2009). However, this correlation may be debatable if the diffuse cytoplasmic staining of RD3 noted previously (de Silva et al 2003) actually represents the non-fibrillary tau deposits found in pretangles.…”
Section: Discussionsupporting
confidence: 94%
“…27 Previous studies demonstrated also that typical NFTs harbor both 3R tau and 4R tau epitopes, while pretangles exhibit 4R tau epitope in AD brains. [28][29][30] However, immunohistochemical visualization suffered from nonspecific staining with RD3 antibody because it sometimes gives diffuse non-specific staining in neuronal cytoplasm resembling so-called pretangles 31 as reported in the initial report on these isoform-specific antibodies. 27 Although such diffuse staining of RD3 raises a possibility that 3R tau deposition characterizes pretangles, similar RD3 staining in normal brain or brains of PSP argues against this possibility.…”
Section: Biochemistrymentioning
confidence: 99%
“…Single staining for RD3 or RD4 disclosed RD4+ pretangles and RD3+ ghost tangles. [28][29][30] However, it was only after successful double staining with RD3 and RD4 that clarified the profile shift from RD4 to RD3. 28,33 Similarly, double immuno EM for 3R and 4R tau, if possible, may disclose ultrastructural details in relation to these epitopes.…”
Section: Current Ambiguities and Future Perspectivementioning
confidence: 99%
“…We had previously developed two monoclonal antibodies; RD3 and RD4, specific for 3R-and 4R-tau isoforms, respectively and these antibodies have now been extensively utilised in several neuropathological studies (de Silva et al, 2003Hogg et al, 2003;Kitamura et al, 2005;Togo et al, 2002). In this paper, we describe the development of the first sandwich ELISAs to quantify 3R-and 4R-tau, using these antibodies.…”
Section: Introductionmentioning
confidence: 97%